Research Progress in Methods to Estimate High-resolution Direction of Arrival - Wei ZHAO; Xuan LI; Chengpeng HAO (水下无人系统学报)
With the widespread application of array signal processing, the estimation of direction of arrival(DOA) as the core problem of array signal processing has made significant progress. This paper first summarizes the traditional algorithms based on beamforming for narrowband target direction estimation relying on uniform linear arrays and emerging algorithms in the past decade. Then, it analyzes the reasons for the limited resolution of traditional beamforming-based methods and discusses higher-resolution methods such as adaptive beamforming direction spectrum, subspace methods, and compressed sensing. Furthermore, for the needs of practical applications, the paper summarizes the progress of broadband target DOA estimation methods, sparse array-based DOA estimation methods, and two-dimensional DOA estimation methods. Finally, the new advances of artificial intelligence-based methods in DOA estimation are introduced. The research in this paper can be applied to modern radar/sonar detection, radio communication, and navigation, showing high application value.